EFISIENSI EKONOMIK PRODUKSI TEMBAKAU WHITE BURLEY SEBAGAI KOMODITI SUBSTITUSI IMPOR DI DAERAH SENTRA PENGEMBANGAN BARU KABUPATEN JEMBER - Supriono, Agus; Sunardi, Sunardi; Sholihin, Miftahus (Jurnal Sosial Ekonomi Pertanian, 2008)
Tobacco is the main commodity in Jember Regency and as the import commodity to generate the devisa. Recently, in the free trade policy the commodity have be able to be efficient. The study concerned to understand the economic efficiency of White Burley Commodity and to understand the sensitivity when any change condition particularly increasing of input price and decreasing of output price and quantity. The method that used is comparative advantages by BSD and CBSD. The result shows that White Burley tobacco production in Jember Regency exactly improved and produced as import substitution product and identified as economic efficiency. Furthermore, a dollar that released for importing need US 0,87 domestic resource. The simulation by decreasing output price as 20% , decreasing production cost as 20% , the international price slow down as10%, so White Burley tobacco production in Jember Regency is economically not efficient.. in deep, the slowing down of international price is the highest one than slowing down of production and the changing of production cost. Key words : economic efficiency, import substitution commodity, domestic resource cost